Behavioural risks in female dogs with minimal lifetime exposure to gonadal hormones - Starling, Melissa (PLoS One, 2019)
Spaying of female dogs is a widespread practice, performed primarily for population control. While the consequences of early spaying for health are still being debated, the consequences for behaviour are believed to be negligible. The current study focused on the reported behaviour of 8981 female dogs spayed before 520 weeks (ten years) of life for reasons other than behavioural management, and calculated their percentage lifetime exposure to gonadal hormones (PLGH) as a proportion of their age at the time of being reported to the online Canine Behavioral Assessment and Research Questionnaire (C-BARQ). We found that 23 behaviours differed between entire and spayed dogs, of which 12 were associated with PLGH and 5 with age-at-spay (AAS). Two behaviours, chewing and howling, were significantly more likely in dogs with longer PLGH. In contrast, longer PLGH was associated with significantly reduced reporting of 10 (mostly unwelcome) behaviours. Of these, one related to fearfulness and three to aggression. The current data suggest that dogs’ tendency to show numerous behaviours can be influenced by the timing of spaying. They indicate how female dog behaviour matures when gonadal hormones are allowed to have their effect. The differences reported here between undesirable behaviours of spayed and entire dogs were in the range of 5.33% and 7.22%, suggesting that, for some dogs, partial or complete denial of maturation may reduce howling and chewing and improve retrieval and recall, but have other undesirable consequences. Veterinarians may take these data into account to discuss the risks and benefits of spaying with clients, and the timing of the procedure.